Atrial Fibrillation Ablation without Interruption of Anticoagulation. (11th April 2011) - Santangeli, Pasquale; Di Biase, Luigi; Sanchez, Javier E.; Horton, Rodney; Natale, Andrea
Abstract : Atrial fibrillation (AF) can be cured by pulmonary vein antrum isolation (PVAI) in a substantial proportion of patients. The high efficacy of PVAI is partially undermined by a small but concrete periprocedural risk of complications, such as thromboembolic events and bleeding. A correct management of anticoagulation is essential to prevent such complications. Performing PVAI without interruption of oral anticoagulation has been demonstrated feasible by our group in previous studies. Recently, we reported that continuation of therapeutic warfarin during radiofrequency catheter ablation consistently reduces the risk of periprocedural stroke/transient ischemic attack without increasing the risk of hemorrhagic events. Of note, interrupting warfarin anticoagulation may actually increase the risk of stroke even when bridged with heparin. The latter strategy is also associated with an increased risk of minor bleeding. With regard to major bleeding, we found no significant difference between patients with a therapeutic INR and those who were bridged with heparin. Therefore, continuation of therapeutic warfarin during ablation of AF appears to be the best anticoagulation strategy. In this paper we summarize our experience with AF ablation without interruption of anticoagulation.